Asymptomatic chronic traumatic aortic valve perforation with severe aortic regurgitation. Issue 7 (17th June 2020) - Bachani, Neeta; Bagchi, Avishek; Sinkar, Kunal; Jadwani, Jaipal; Dhirawani, Bhavik; Shah, Harshad Pradeep; Vichare, Sanjeev; Pinto, Brian
Abstract: Here, we present a young asymptomatic male patient incidentally diagnosed to have aortic regurgitation (AR). The patient had a history of a blunt trauma to the thorax two years back but did never have any symptoms. Transthoracic echocardiography showed a moderately dilated left ventricle with normal systolic function and severe AR with normal nondilated aortic root and tri‐leaflet aortic valve. To diagnose the etiology of the AR, a transesophageal echocardiogram (TEE) was done, which revealed a perforation in the nonadjacent leaflet (NAL) and confirmed severe AR with two AR jets being clearly visualized, one through the point of incomplete coaptation and other one through the perforated area in the NAL. The patient was treated with aortic valve replacement and was doing well on follow‐up.